Absent Ureteral Efflux after Hysterectomy Leads to Diagnosis of Ureteral Atresia with Renal Atrophy - Olga Mutter; Ekaterina Grebenyuk; Arleen Ayala-Crespo; Kevin Yang (Case Reports in Obstetrics and Gynecology)
Iatrogenic injury to the urinary system is a known complication of gynecologic surgery; therefore, intraoperative cystoscopy is frequently performed to assess for such injuries. However, if an abnormality is seen, the differential diagnosis extends beyond iatrogenic causes. A 42-year-old patient underwent a total abdominal hysterectomy and had absent efflux from the right ureteral orifice on cystoscopy. While iatrogenic injury was initially suspected, the intraoperative workup (including intravenous pyelography (IVP)) that ensued led to an empiric diagnosis of right ureteral atresia with ipsilateral renal atrophy that was then confirmed on postoperative imaging. When an abnormality is seen on cystoscopy following gynecologic surgery, it is important to maintain a broad differential diagnosis and to pursue an intraoperative workup with early involvement and close collaboration with urology.